1986
DOI: 10.1021/j100276a042
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-atom abstraction from alkanes by hydroxyl. 2. Ethane

Abstract: Absolute rate coefficients for the reactions of OH with C2H6 (kl), C2H3D3 (k2), and C2D6 ( k 3 ) were measured with the laser photolysis/laser-induced fluorescence technique. Kinetic data were obtained at 600 torr of helium pressure over the temperature range 292.5-705 K. The measurements were fit to modified Arrhenius expressions of the form ki(T) = Ail'" exp(-Ei/Rr). Kinetic isotope effects were characterized by two simple relations: k2(T) = 0.5[k1(T) + k 3 ( T ) ] , and k l ( T)/k3(T) = (1.01 A 0.06) exp(90… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
71
1

Year Published

1986
1986
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(78 citation statements)
references
References 1 publication
6
71
1
Order By: Relevance
“…For each set of experiments, the difference between the value of k 0 directly measured in the absence of bromine and k 0 found from the zero-abscissa intercept of the least-squares straight line in the ([Br 2 ], k′) coordinates was within the experimental uncertainties (2σ level of statistical uncertainties obtained from the linear least-squares-fits). We analyzed the possible effect of a minor deviation from the first-order kinetic behavior of the OH background loss on the measurement of k 1 values using data processing with the background-loss correction described in references 10, [16][17][18][19]. Under all the experimental conditions in our study, it was found that this effect was very small (less than 0.8% of k 1 value) such that no background-loss correction was necessary.…”
Section: B Reaction Rate Measurements and Resultsmentioning
confidence: 93%
“…For each set of experiments, the difference between the value of k 0 directly measured in the absence of bromine and k 0 found from the zero-abscissa intercept of the least-squares straight line in the ([Br 2 ], k′) coordinates was within the experimental uncertainties (2σ level of statistical uncertainties obtained from the linear least-squares-fits). We analyzed the possible effect of a minor deviation from the first-order kinetic behavior of the OH background loss on the measurement of k 1 values using data processing with the background-loss correction described in references 10, [16][17][18][19]. Under all the experimental conditions in our study, it was found that this effect was very small (less than 0.8% of k 1 value) such that no background-loss correction was necessary.…”
Section: B Reaction Rate Measurements and Resultsmentioning
confidence: 93%
“…Here, we present the quantification obtained by assuming that (1) the reactivity of a given methyl or methylene group can be suppressed by deuterium substitution without altering the reactivity of the neighboring carbon sites and (2) that the impact of deuteration can be quantified. Tully and co-workers 11,21,22 made the first assumption in their studies of deuterated propanes to determine the reactivity of individual methylene and methyl groups for both hydrogen and deuterium as a function of temperature. The ab initio calculations of Hu et al 23 confirmed, to a first approximation, the reactivity of an individual abstraction site was independent of neighboring alkyl groups.…”
Section: Measurements Of Oh + Bromopropane Isotopomers K 2 -(T)-k 5 mentioning
confidence: 99%
“…Various approximations have been used in the literature, such as the Next-Nearest-Neighbor (NNN) [5,6] and Structure Activity Relationship (SAR) [7]. Tully and co-workers [8][9][10][11][12][13] pioneered the use of deuterium for the study of deuterium kinetic isotope effect (DKIE) to elucidate rules for the calculation of sitespecific rates of H-abstraction from a variety of hydrocarbon molecules. This methodology has, for example, been used to discern the branching ratios of the two competing channels during the reaction of propane (C 3 H 8 ) with OH at low temperatures [10] and high temperatures [14].…”
Section: Introductionmentioning
confidence: 99%
“…The aim of the current work is to extend low-temperature (290-800 K) DKIE data of ethane [9] to high temperatures (800 -1350 K) using rate coefficient measurements of the reaction of ethane and deuterated ethane with OH radicals:…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation